The Educational Implications of the Atomistic Family Structure: How the Atomization of the Family Undermines the Education of Critical Citizens by Making People Vulnerable to Indoctrination and Propaganda - Puolimatka, Tapio (Acta Paedagogica Vilnensia, 2017)
This article uses historical and sociological research as the basis for a philosophically argued thesis about the negative educational consequences of the atomization of the family structure. Carle Zimmerman’s theory of the social causality involved in the atomistic family structure is illustrated with an example of a Bolshevik social experiment and applied to the atomization of the modern Western family as shown by contemporary social science research. The focus is on the ways that the atomization of the family undermines the education of children into autonomous and critical citizens. Once the normative structures of marriage and family disintegrate, the identity and relationship rights of children are violated. This violation is often experienced by children as a rejection. Such a rejection wounds children morally and undermines their faith in moral norms. Furthermore, the disintegration of the family leaves children in a state of emotional and moral deprivation, which undermines their ontological security and their development into autonomous moral agents and critical citizens. By exposing them to the emotional influence of the cultural myths used in propaganda and indoctrination, these deprivations make them externally-directed instead of developing their capacity for autonomous deliberation and independent moral agency. Insofar as citizen’s views and attitudes are directed from the outside, they fail to function as a counterbalance to the ruling elites, and democracy deteriorates into elite rule.